Influences of Regional Diffusion of Democratic Strategies in Nigeria from Neighbouring African States - Gar, Ruqayya, Aminu; Umar, Mohammed, Nuru; Muhammad, Murtala (My University, 2022)
Regional imitation is a propensity aimed at neighbouring nations to meet toward a common level of democratic political development. One can understand how such a propensity exists by concentrating on a diffusion element that analyses the hypothetically anticipated outcome of electoral management policies in these neighbouring nations. Research on Nigeria’s democracy exist however, concentrated exclusively on domestic phenomenon and factors such as socio-cultural cleavages, overlooking the likely external influence of international norms, and regional diffusion of democratic strategies from neighbouring African states. This study examines the influences of regional diffusion of democratic strategies on Nigeria’s democratic development, through a qualitative process of data collection and analysis. The study concludes that, regional diffusion of democratic strategies from successful wave of democratic transition to opposition parties against the then incumbent ruling political parties in African countries, such as Senegal, Mauritius, Ghana, Uganda, Malawi and Mali has motivated people and institutions in Nigeria to emulate the development there. Particularly, strong adherence to the rule of law by political actors, independence and integrity of the legal system, and provision of efficient civic and voter education have greatly motivated and influenced the change in Nigeria’s democratic development strategies.
Keywords: African States; Democratic; Diffusion; Nigeria; Regional; Strategies